The Reasons of Considering Ethics in Accounting Job - Azam Meymandi; Hossein Rajabdorri; Ziba Asoodeh (International Journal of Management, Accounting and Economics, 2015)
In the current commercial environment, the role of accountants is important. Indeed, accountants have key role in success and dynamics of organizations. Based on their vital role in organization, it can be said we can rely on the accountants and the results of their work as we can consider suitable level of professional ethics. Achieving accounting goal without ethics is impossible. Indeed, the society has great expectations of these people and the people should trust in the services presented by this group. Thus, the information presented by accountants should be reliable and non-biased. Thus, accountants should have high honesty. This study investigates the role of ethics in accounting.